Adsorpsi Methyl Violet oleh Karbon Aktif dari Limbah Tempurung Kelapa dengan Aktivator ZnCl2 Menggunakan Pemanasan Gelombang Mikro - Widi Astuti; Anggelita Dwi Handayani; Diah Ayu Wulandari (Jurnal Rekayasa Kimia & Lingkungan, 2018)
Synthesis of activated carbon from coconut shell waste with ZnCl2 activation using microwave heating have been carried out. Coconut shell consists of 36.51% lignin, 33.61% cellulose and 19.27% hemicellulose which causes it can be used as a precursor in the synthesis of activated carbon. The activated carbon was further characterized using Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectrophotometer (FTIR) and NOVA Gas Sorption Analyzer-Quantachrome and used for the adsorption of methyl violet in aqueous solution with variation of pH, contact time and concentration of solution. The result showed that the pore of activated carbon was larger than that of the char. The optimum adsorption occurred at pH 3 and the equilibrium time was reached after 180 minutes. The Langmuir equilibrium model was more appropriate than the Freundlich equilibrium model. While the kinetics model analyzed using pseudo first order, pseudo second order, internal diffusion and external diffusion indicated that the pseudo second order was most suitable for the adsorption of methyl violet by coconut shell activated carbon.